Silyldienolates in Organocatalytic Enantioselective Vinylogous Mukaiyama-Type Reactions: A Review - Leon Hoppmann; Olga García Mancheño (Molecules, 2021)
Mukaiyama aldol, Mannich, and Michael reactions are arguably amongst the most important C–C bond formation processes and enable access to highly relevant building blocks of various natural products. Their vinylogous extensions display equally high potential in the formation of important key intermediates featuring even higher functionalization possibilities through an additional conjugated C–C double bond. Hence, it is much desired to develop highly selective vinylogous methods in order to enable unconventional, more efficient asymmetric syntheses of biologically active compounds. In this regard, silyl-dienolates were discovered to display high regioselectivities due to their tendency toward γ-additions. The control of the enantio- and diastereoinduction of these processes have been for a long time dominated by transition metal catalysis, but it received serious competition by the application of organocatalytic approaches since the beginning of this century. In this review, the organocatalytic applications of silyl-dienolates in asymmetric vinylogous C–C bond formations are summarized, focusing on their scope, characteristics, and limitations.